Ab? Sa'id al-Hadim ?'s Approach to Some Issues in the Science of Hadith In the Specialization of In the context of Maj?mi‘ al-Hak?iq ve’l-Qawaîd and Risale fî Hakki’l-Hadith’d-Da‘îf - Kazan, Tahsin (Siirt University, 2025)
The words, actions and behaviors of the Prophet (pbuh) are called hadith. Hadiths are the second main source of Islamic sciences after the Qur'an. Scholars have made great efforts to transmit the hadiths of the Prophet to subsequent generations through authentic means. As part of this effort, scholars of hadith paid due attention to important principles such as “tesebbüt” and “taharrî” in their studies of hadith. After the death of the Prophet, this scientific activity in the tahammul reception and ad?’ delivery of the hadiths has continued from the first generation to the present day. Hadith scholors continued the process of collecting and classifying hadiths without interruption. Each successive scholar has endeavored to continue and develop the scholarly tradition from where the previous generation left off. Ab? Sa?d al-Kh?dim? (d. 1176/1762), an Ottoman scholar who lived in the 18th century, was also a scholar who served Islamic sciences in general and hadith science in particular. al-Kh?dim? is a scholar who has written works in many scientific disciplines, especially his treatises. He dealt with some issues related to the hadith methodology in his work titled “Maj?mi‘ al-?ak?iq” which he wrote on the Us?l al-fiqh. Although al-Kh?dim? benefited mostly from Ibn Hajar's Nuhbet al-fiker in his understanding of usul, he is also important in terms of providing information about the approaches of these two schools in hadith methodology due to his Sufi orientation aspect and his affiliation with the Hanafi school. Although there are no fundamental differences between Ahl al-Hadith and the Hanafi school, which is accepted as Ahl al-Rayy, on issues related to hadith, there are differences observed in some matters. In this study, al-H?dim?'s Maj?mi'u'l-?aq?'iq and Ris?latun f? haqqi'l-had?th al-da'?f, which he wrote about weak had?th, are taken as basis and the basic issues of had?th methodology are analyzed. The fact that the mentioned work of al-Kh?dim? is a book of figh methodology is also important in terms of determining the points where the fuqahas think differently from the hadith scholors. This article is not limited to these two works of the author, but also other works related to this branch of science are occasionally referred to. Since it is a concise text, Menâfi?u’d-dekâik, which is the commentary written on Maj?mi‘ al-?ak?iq has been benefited to the maximum extent.

Hz. Peygamber’in (s.a.v.) söz, fiil ve davranışlarına hadis denilmektedir. Hadisler İslâmî ilimlerde Kur’ân’dan sonra gelen ikinci aslî kaynaktır. Âlimler, Hz. Peygamber’in hadislerini sahih yollarla sonraki nesillere nakletmek için yoğun gayret sarf etmişlerdir. Bu gayretin bir parçası olarak muhaddisler hadis çalışmalarında, tesebbüt ve taharrî gibi önem arz eden ilkelere gereken ihtimamı göstermişlerdir. Hz. Peygamber’in irtihalinden sonra hadislerin tahammül ve edâsında ilk nesilden günümüze kadar bu ilmî faaliyet devam etmiştir. Muhaddisler hadisleri tespit, tedvin ve tasnif işlemine aralıksız devam etmişlerdir. Her gelen âlim, seleflerinin bıraktığı yerden ilmî geleneğin devamı ve tekamülü için gayret sarf etmiştir. 18. asırda yaşamış Osmanlı âlimi Ebû Saîd Hâdimî de (öl. 1176/1762) genelde İslâmî ilimlere özelde de hadis ilmine hizmet etmiş bir bilgindir. Hâdimî başta risâleleri olmak üzere birçok ilmî disiplinde eser yazmış bir âlimdir. Usûl-i fıkha dair yazmış olduğu Mecâmi’u’l-hakâik başlıklı eserinde hadis usûlü ile ilgili bazı konuları ele almıştır. Hâdimî, usûl anlayışında daha çok İbn Hacer’in Nuhbetü’l-fiker’inden yararlanmışsa da; tasavvufî yönü ve Hanefî mezhebine mensubiyeti dolayısıyla hadis usûlünde bu iki ekolün yaklaşımı ile ilgili bilgiler vermesi açısından da önem arz etmektedir. Ehl-i hadis ile ehl-i rey olarak kabul edilen Hanefî mezhebi arasında hadisle ilgili mevzularda temelde anlaşmazlık olmamakla birlikte bazı hususlarda farklılıkların olduğu görülür. Bu çalışmada Hâdimî’nin Mecâmi’u’l-hakâik ve zayıf hadis hakkında yazmış olduğu Risâletün fî hakki’l-hadis’d-da‘îf risâlesi esas alınarak hadis usûlünün temel konuları incelenmiştir. Hâdimî’nin mezkûr eserinin fıkıh usûlü kitabı olması, fukahânın muhaddislerden farklı düşündükleri noktaları tespit açısından da önem arz etmektedir. Bu makalede müellifin bu iki çalışmasıyla iktifa edilmemiş, yer yer bu ilim dalı ile ilgili diğer eserlere de müracaat edilmiştir. Muhtasar bir metin olması hasebiyle Mecâmi’u’l-hakâik’e yazılmış şerh olan Menâfi?u’d-dekâik fî şerhi Mecâmi?i’l-hakâik’ten de azami derecede istifade edilmiştir.
Mecâmiu’I-hakâyik ve’l-kavâid ve Risâletün fî hakki’l-hadis’d-da‘îf Özelinde Ebû Saîd el-Hâdimî’nin Hadis İlminin Bazı Meselelerine Yaklaşımı
Keywords: Hadith; Hadis